THE ROLE OF FINE ARTS IN SPIRITUAL EDUCATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, the role of fine art in the formation of spiritual education is analyzed on the example of the rarest examples of various rock paintings preserved in Uzbekistan, the interpretation of their images.